Impaired Glymphatic System Actions in Obstructive Sleep Apnea Adults - Roy, Bhaswati; Nunez, Alba; Aysola, Ravi S.; Kang, Daniel W.; Vacas, Susana; Kumar, Rajesh (Frontiers in Neuroscience, 2022)
Study Objectives Obstructive sleep apnea (OSA) is accompanied by sleep fragmentation and altered sleep architecture, which can potentially hinder the glymphatic system, increasing risks for Alzheimer’s disease (AD), but the status is unclear in OSA. Our aim was to investigate the glymphatic system in OSA subjects and examine the relationships between OSA disease severity, sleep symptoms, and glymphatic system indices in OSA using diffusion tensor imaging (DTI). Methods We acquired DTI data from 59 OSA and 62 controls using a 3.0-Tesla MRI and examined OSA disease severity and sleep symptoms with the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). Diffusivity maps in the x-axis (Dxx), y-axis (Dyy), and z-axis (Dzz), as well as in x-y axis (Dxy), y-z axis (Dyz), and x-z axis (Dxz) were calculated, diffusion values for the projection and association fibers extracted, and the DTI analyses along the perivascular space (DTI-ALPS index) were performed. The glymphatic system indices were compared between groups and correlated with disease severity and sleep symptoms in OSA subjects. Results Dzz values, derived from projection fiber areas, Dyy and Dzz values from association fiber areas, as well as ALPS and Dyzmean values were significantly reduced in OSA over controls. Significant correlations emerged between disease severity, sleep symptoms, and Dxy, Dxx, and Dzz values in OSA subjects. Conclusion OSA patients show abnormal glymphatic system function that may contribute to increased risks for AD. The findings suggest that the APLS method can be used to assess the glymphatic system in OSA patients.